Diet and Behavior of Macaca fascicularis for Ecotourism Contributing on Pengsong Area - M. Yamin; Dadi Setiadi; Khairuddin Khairuddin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Mount Pengsong is a mountainous ecotourism area with beautiful natural scenery and interesting biodiversity, including the presence of Macaca fascicularis populations. Type of food Macaca fascicularis in the tourist area of Mount Pengsong is not yet known, including itÃ¢â¬â¢s carrying capacity for population numbers. This study aims to determine the types of plants eaten and the types of food provided by visitors as well as the nutritional content of food consumed by monkeys in the area and the behavior of Macaca fascicularis as a management basis to support ecotourism in Mount Pengsong.ÃÂ Data were collected using the